Constraints Experienced by Teachers in Utilization of Educational Technology: A Study in State Agricultural University - Rakshit , Shantanu; Sharma, Gyanendra (Indian Journal of Extension Education, 2015)
The study was conducted in Govind Ballabh Pant University of Agriculture and Technology, Pantnagar. Acomprehensive  and detailed pre-tested questionnaire was used for collecting information. Fifty per cent of teachers from each college  were selected randomly in sample. Total 120 completely answered questionnaires were received. The respondents were  asked to express the constraints in the utilization of educational technologies. The mean score for a particular constraint  was worked out by dividing the weighted score of the constraints by the total number of respondents. The ranking of  constraints was done according to the mean score of each statement. Lack of technical support was perceived as most  important constraint. Other important constraints were lack of maintenance of existing facilities; lack of funds; lack of  supporting hardware and software; and lack of periodic reviews of the digital learning materials. Majority of the important  constraints are related with infrastructure and administration.
Keywords: Educational technology; constraints; agricultural university